Gene and protein expression in human megakaryocytes derived from induced pluripotent stem cells. (6th May 2021) - Kammers, Kai; Taub, Margaret A.; Mathias, Rasika A.; Yanek, Lisa R.; Kanchan, Kanika; Venkatraman, Vidya; Sundararaman, Niveda; Martin, Joshua; Liu, Senquan; Hoyle, Dixie; Raedschelders, Koen; Holewinski, Ronald; et al.
Abstract: Background: There is interest in deriving megakaryocytes (MKs) from pluripotent stem cells (iPSC) for biological studies. We previously found that genomic structural integrity and genotype concordance is maintained in iPSC‐derived MKs. Objective: To establish a comprehensive dataset of genes and proteins expressed in iPSC‐derived MKs. Methods: iPSCs were reprogrammed from peripheral blood mononuclear cells (MNCs) and MKs were derived from the iPSCs in 194 healthy European American and African American subjects. mRNA was isolated and gene expression measured by RNA sequencing. Protein expression was measured in 62 of the subjects using mass spectrometry. Results and Conclusions: MKs expressed genes and proteins known to be important in MK and platelet function and demonstrated good agreement with previous studies in human MKs derived from CD34+ progenitor cells. The percent of cells expressing the MK markers CD41 and CD42a was consistent in biological replicates, but variable across subjects, suggesting that unidentified subject‐specific factors determine differentiation of MKs from iPSCs. Gene and protein sets important in platelet function were associated with increasing expression of CD41/42a, while those related to more basic cellular functions were associated with lower CD41/42a expression. There was differential gene expression by the sex and race (but not age) of the subject. Numerous genes and proteins were highly expressed in MKs but not known to play a role in MK or platelet function; these represent excellent candidates for future study of hematopoiesis, platelet formation, and/or platelet function.